Shamanic Eroticism in the Jiu ge (Nine Songs) of Early China. Issue 1 (31st May 2017) - Michael, Thomas
Abstract : This article presents an analysis of certain erotic strategies employed by shamans of the early Chinese state of Chu that were intended to attract and seduce an array of spirits thought to inhabit the world of nature. These strategies are analyzed from a collection of songs gathered together under the title of the Jiu ge from the Chuci anthology, and they provide some of the clearest evidences for a tradition of early Chinese southern Chu shamanism. After setting forth certain elements of the religious, historical, and theoretical background of this shamanism, this article approaches and analyzes it in terms of the eroticized gender relations between humans and spirits upon which this shamanism is centrally based. Because the present author understands shamanism in terms of face to face communication between human beings and bodiless beings in a séance event, and because these communications are represented as taking place by way of either the shaman journeying to the spirit or the spirit coming to take possession of the shaman, the final sections of this article analyze each type of séance event separately.